Social integration and confidence in the police: a cross-national multi-level analysis - Choi, Jaeyong (Policing and society, 2021)
Building on the insight of Durkheim, the current study examines the hypothesis that cross-national proxies for social integration explain variation in confidence in the police across different countries. Combining six sources of data from 84 nations with a total sample size of 122,330 respondents, the current research uses hierarchical generalised linear modelling (HGLM) logistic regression analyses to investigate the potential mechanism of social integration in shaping confidence in the police. Results show that three proxies of social integration (i.e. homicide rates, group grievance, and suicide rates) are negatively and significantly associated with confidence in the police. Additionally, results replicated the U-shaped convex curvilinear relationship between democracy and police confidence. Durkheim’s notion of social integration can offer a theoretical framework to account for the effects of country-level variables on confidence in the police across cultural boundaries.